Một số vấn đề cơ bản của hệ điều hành thời gian thực - Tân, Phan Minh (Journal of Computer Science and Cybernetics, 2016)
This paper is concerned with the design of operating systems for realtime or online computer systems. An online or realtime operating system must respond to all critical demands in restricted times promply. After presenting the functions and  principles of design, some examples of using Realtime Operating System  in  measurement and control are given for illustration.